Dental students' familiarity with the medical management of dental patients at Brazilian dental schools - Araújo, Paula Caetano; Garbin, Clea Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Arcieri, Renato Moreira [UNESP] (My University, 2013)
Drug therapy in dentistry is essential for patients' treatment and requires special care by dentists, so it must be part of a well-grounded education for predoctoral dental students. The aim of this study was to evaluate the knowledge of undergraduate students at dental schools in Brazil about the use of drugs in dental practice. The sample universe was comprised of all undergraduates enrolled in the last year of the dentistry course in three universities in 2010 (n=253). Inclusion criteria were students in their last year of enrollment and who agreed to participate in the research. The results were analyzed on Epi Info 3.5.1 software. Analyses were conducted with chi-square, Friedman, and Wilcoxon tests. Slightly more than half of the participants (51.9 percent) reported the ideal dose of anesthetic for a normal patient. However, their difficulties increased when asked about the relationship between the anesthetic and patients with systemic disease or those needing special care. Regarding drugs that usually cause allergic attack, only 29.2 percent and 36.6 percent, respectively, cited methyl methacrylate and latex. This study found that the knowledge of these undergraduates about the questions was deficient, so dental education should include more theoretical and clinical practice in recognizing the patient's medical needs.
Keywords: Brazil; Dental anesthesia; Dental materials; Dental students; Drug therapy in dentistry; biomedical and dental materials; dental material; local anesthetic agent; methacrylic acid methyl ester; penicillin derivative; teratogenic agent; allergy; cross-sectional study; dental anesthesia; dental education; dental procedure; dental student; dental students; drug contraindication; drug hypersensitivity; drug therapy; drug therapy in dentistry; education; human; hypersensitivity; medication therapy management; dental materials; Anesthetics, Local; Cross-Sectional Studies; Dental Care for Chronically Ill; Dental Care for Disabled; Drug Hypersensitivity; Drug Therapy; Education, Dental; Humans; Hypersensitivity; Latex Hypersensitivity; Medication Therapy Management; Methylmethacrylate; Penicillins; Pharmaceutical Preparations, Dental; Students, Dental; Teratogens